Obesity and childhood diabetes as aggravating conditions of COVID-19 in children in the West of Paraná (Research, Society and Development, 2023)
COVID-19, a respiratory illness caused by the SARS-CoV-2 coronavirus, has been a global concern due to its strength and impact on public health. The virus spreads mainly through respiratory droplets, when an infected person coughs, sneezes or talks, but it can also be acquired through contact with contaminated surfaces. When in the human body, it enters the lungs through the enzyme ECA2.This study aimed to investigate whether there is a higher incidence of severe cases of COVID-19 in obese and/or diabetic children compared to healthy children. For this, a quantitative, observational and cross-sectional study was carried out using data provided by the Division of Epidemiological Surveillance of Cascavel, involving pediatric patients up to 12 years old.The results of the analysis of COVID-19 cases in children revealed that the incidence of severe cases was significantly higher in children with diabetes and/or obesity. This finding suggests an association between obesity/diabetes and greater severity of COVID-19 infection in children.These findings are important for public health and highlight the need for specific policies and interventions to prevent and treat obesity and diabetes in children. In addition, they highlight the importance of preventive measures, such as vaccination, to protect children against COVID-19 and reduce the risk of serious complications.